Anomalies of precipitation and drought in objectively derived climate regions of Iran - Ghaedi, Sohrab (Hungarian Geographical Bulletin, 2021)
By regionalizing precipitation in 113 synoptic stations in Iran, the characteristics of precipitations and the occurrence of droughts in each region were investigated over a period of 30 years, 1988–2017. Elevation, latitude and distance from moisture source have caused strong East–West and South–North gradients of precipitation across the territory of Iran so that the average annual precipitation increases from 55 mm in the eastern and central regions to 1,730 mm in the south-west coast of the Caspian Sea. Hierarchical cluster analysis identified six precipitation regions in Iran, including the arid, semi-arid, moderate, semi-humid, humid, and high humid regions. An investigation of the standardized precipitation index (SPI) showed that the trend in about 19 per cent of stations was significantly decreasing. It was non-significantly decreasing in 65 per cent, significantly increasing in less than 1 per cent, and non-significantly increasing in 15 per cent of the stations. While the occurrence of drought has increased in most parts of Iran, it has decreased in some stations only in the northern strip of the country. The line slope in more than 84 per cent of the stations represent negative values in SPI, which confirms an increase in the occurrence of droughts in Iran.